What is the best pharmacologic treatment for gastroparesis?. Issue 9 (September 2016) - Lee, Jonathan; Keller, Scott
Abstract : Evidence‐Based Answer : Metoclopramide, erythromycin, and domperidone appear to similarly improve symptoms of gastroparesis; the single best treatment is unclear (SOR: B, systematic reviews of poor‐quality RCTs and observational studies and 2 small RCTs). Domperidone appears to produce fewer and less severe central nervous system (CNS) adverse effects than metoclopramide (SOR: B, single RCT).